2022
DOI: 10.3389/fendo.2021.775677
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Rich Lipoproteins and Glycoprotein A and B Assessed by 1H-NMR in Metabolic-Associated Fatty Liver Disease

Abstract: High plasma triglyceride (TG) levels and chronic inflammation are important factors related to metabolic-associated fatty liver disease in patients at cardiovascular risk. Using nuclear magnetic resonance (1H-NMR), we aimed to study the triglyceride-rich lipoprotein (TRL) and acute-phase glycoprotein profiles of a cohort of patients with metabolic disease and their relationship with fatty liver. Plasma samples of 280 patients (type 2 diabetes, 81.1%; obesity, 63.3%; and metabolic syndrome, 91.8%) from the Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
4
2
Order By: Relevance
“…15,16,[24][25][26][27] The robustness of these NMR-measured glycoproteins improves the detection of systemic inflammation to a wider extent than single markers, such as high-sensitivity CRP. 19,28 In our study, we could not detect differences in this clinically established marker, whereas the concentrations of Glyc-A, B and F increased in parallel to TRL-TG levels. These results suggest that TRL concentrations and composition have a significant impact on the subclinical inflammatory status of patients with lipid metabolism derangements.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…15,16,[24][25][26][27] The robustness of these NMR-measured glycoproteins improves the detection of systemic inflammation to a wider extent than single markers, such as high-sensitivity CRP. 19,28 In our study, we could not detect differences in this clinically established marker, whereas the concentrations of Glyc-A, B and F increased in parallel to TRL-TG levels. These results suggest that TRL concentrations and composition have a significant impact on the subclinical inflammatory status of patients with lipid metabolism derangements.…”
Section: Discussioncontrasting
confidence: 74%
“…In our study, patients in the highest quartile of TRL‐TG showed higher levels of TRL particles as well as Glyc‐A, B and F. Recently, we and others have provided evidence that these liver‐derived glycoproteins are reliable biomarkers of low‐grade systemic inflammation in different conditions, including infectious and autoimmune diseases, T2DM, hypertension and atherosclerotic cardiovascular disease 15,16,24–27 . The robustness of these NMR‐measured glycoproteins improves the detection of systemic inflammation to a wider extent than single markers, such as high‐sensitivity CRP 19,28 . In our study, we could not detect differences in this clinically established marker, whereas the concentrations of Glyc‐A, B and F increased in parallel to TRL‐TG levels.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…These were consistent with our experimental results. Clinically, AST and ALT are commonly used to re ect human liver function, and the liver function plays an important role in lipid metabolism [23]. LDH mainly exists in animal tissues such as myocardium and liver.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease and chronic infection status, as in HIV patients, also have higher GlycA levels. [19][20][21][22][23][24] GlycF represents different glycosylation molecules not bound to proteins, and its biological role has been less studied. Overall, the 3 signal pics of glycosylated proteins designate different aspects of the same global biochemical process.…”
mentioning
confidence: 99%